Normal phase HPLC-based activity profiling of non-polar crude plant extracts – acetylcholinesterase inhibiting guttiferones from Montrouziera cauliflora as a case study. Issue 24 (16th December 2016) - Landreau, Anne; Bertrand, Samuel; Simoes-Pires, Claudia; Marcourt, Laurence; Taï, Dang Bach; Litaudon, Marc; Guilet, David; Richomme, Pascal; Carrupt, Pierre-Alain; Wolfender, Jean-Luc
Abstract: The study describes bioactive compounds as inhibitors of acetylcholinesterase (AChE), from the stem bark extract of Montrouziera cauliflora, selected among 19 dichloromethane extracts from Clusiaceae species. Our work focused on the development of an original normal phase HPLC microfractionation strategy to rapidly assess highly active zones from this crude active non-polar plant extract. Two different microfraction collection methods were evaluated for the assessment of the AChE inhibition. Two guttiferones and a tocotrienol were directly isolated among five compounds identified off-line by NMR after upscaling the fractionation and their AChE inhibition was evaluated. The strengths and weaknesses of the two microfractionation collection methods for HPLC-AChE activity-based profiling are discussed. Abstract :